NATO, Neutrality and National Identity: the case of Austria and Hungary - Kovác, András (2003)
When the cold war was over, a vehement discussion of the new alternatives in security policy started in almost all former Warsaw-Pact States and in the neutral and nonaligned nations, Austria and Hungary among the latter. These nations' entry into the NATO has been the pivotal question. These discussions were the subject of comparative research that was done in Hungary and Austria. The results are presented in the book "NATO, Neutrality and National Identity - the Case of Ausria and Hungary". The book does not focus on the manifold security problems that the concerned nations' joining of NATO would entail but deals with the discourses and debates on neutrality and NATO. The argumentation strategies that were applied in these discourses and debates touch on important motives of national identity and are thus creating identity. Moreover, the NATO discussion is a discussion on security policy and national identity at the same time. The authors' intention was to clarify the dimension relating to identity in the NATO discussion by analyzing the argumentation strategies that were used by the advocates and opponents of NATO membership and the reception of typical arguments in various public opinions. In many cases the argumentation strategies are based on historicizing ways of thinking which claim that there are historical reasons for choosing either of the alternatives (NATO or neutrality). In Hungary, discussions focus on the question whether Hungary is historically an organic part of Europe or whether its own identity will only materialize if the nation adopts a special course between the western and the eastern world. In Austria, the consequences of a potential renunciation of neutrality, one of the most important elements of modern Austrian identity, has been made a subject of passionate discussion. The book analyzes the issues of creating identity by discussion both from a historical-sociological standpoint and from the angle of discourse analysis. The individual chapters deal with comparative studies of the change and upheaval in the national identities in Hungary and Austria. Although these specific analyses are intended to be case studies, they allow generalizations on all of central Europe. The individual corpora (opinion surveys, political speeches, focus groups, talk-shows, newspapers), having been selected so as to ensure comparability, are subjected to a comparative and interdisciplinary analysis and interpretation. Following the introduction - problems are defined from the standpoint of history and political science - the complex discourses from focus group discussions and the outcomes of opinion surveys are presented and analyzed, and newspapers, TV talk-shows and speeches held on days of remembrance are presented applying the methods of discourse analysis. Against this backdrop a comprehensive picture of the identity discourses develops. In the introduction and concluding remarks the two editors draw theoretical and methodical conclusions for interdisciplinary and comparative studies.